ANALISA ERGONOMI MAKRO PADA PENGGUNAAN TELEPON GENGGAM (HANDPHONE) DIKALANGAN MAHASISWA BANDUNG - Kiki Abdul Muluk (Sainteks: Jurnal Sain dan Teknik, 2020)
Along with the rapid development of digital technology, electronic technology which is the forerunner of information and communication technology, has been spurred on by developing miniaturization of electronic components, through the creation of integrated circuits, which at its peak gave birth to communication devices in the form of mobile phones (Cellphones / Cellphones). In its use based on macro ergonomics analysis, cell phone use is hindered by these students, giving positive and negative influences. towards its users. In this study a macro ergonomic analysis was carried out on the use of mobile phones among students, especially students of Industrial Engineering courses, Faculty of Engineering, Bandung Raya University. The purpose of this study is to analyze the positive and negative effects on the use of mobile phones among students in terms of macro ergonomics, related to the use of mobile applications in the learning process with the development of Mobile Learning through the SIAKAD and Edlink programs, and their use in relationships in the campus environment. . The research was conducted with a survey research method approach with a quantitative approach. Data obtained from the results of questionnaires that research in the field, interviews and literature studies. The results of the study showed that the results of the questionnaire test showed that the questionnaire had a level of validity of 85% and 89.6%. The results based on macro ergonomic analysis of the positive effect felt by students, in essence, is that mobile phones are very helpful in various learning process activities, academic activities and other activities in the campus environment, which is currently being promoted by the online system. The negative influence of mobile phones among students, is more on the problem of changing attitudes and behaviors of students which leads to consumptive attitudes, lazy to read text books, tend to reduce direct social interaction and less concern for the surrounding environment.